The characteristics and alteration of peripheral immune function in patients with multiple system atrophy - Wang, Minghui; Yan, Zhaofen; Wang, Jing; Yang, Yujiao; Deng, Qinqin; Han, Yixian; Zhang, Liping; Yang, Huajun; Pan, Jiali; Wang, Mengyang (Frontiers in Neurology, 2023)
Objective Multiple system atrophy (MSA) is a degenerative disease. Immune dysfunction found to play a crucial role in the pathogenesis of this disease in the literature, while the characteristics of peripheral immune function remain unclear. This study aimed to investigate the characteristics and alterations of peripheral immune function in patients with MSA. Methods A case–control study was conducted between January 2021 to December 2022 at SanBo Brain Hospital, Capital Medical University, Beijing, China. A total of 74 participants were recruited, including 47 MSA patients and 27 non-MSA participants. Peripheral blood samples were collected from each participant. A total of 29 types of immune cells were measured using the flow cytometry analysis technology. Single-factor analysis and multiple-factor analysis (multiple linear regression models) were performed to determine the differences and risk factors in immune cells between the MSA and non-MSA groups. Results Alterations of the count or percentage of CD19+ B lymphocytes and CD3−CD56+ B lymphocytes in MSA patients were found in this study. The reductions of the count and percentage of CD19+ B lymphocytes were still robust after adjusting for variables of age, gender, body mass index, albumin, and hemoglobin. Furthermore, the reductions in the count and percentage of CD19+ B lymphocytes in the MSA patients were more significant in women and individuals aged 60 years old or above than in the non-MSA participants. Conclusion Our findings suggested that MSA patients may be influenced by B lymphocytes, particularly CD19+ cells. Therefore, the reductions in immune cells should be considered in the diagnosis and treatment of MSA. Further studies are warranted to confirm and expand upon these findings.